Revitalisasi Tari Mosau’ Bolaang Mongonow Melalui Penciptaan Tari Sinungkudan - Fahrurozy Ambaru Harun; Riana Diah Sitharesmi; Nurlia Djafar (Lembaga Pengembangan Kinerja Dosen, 2026)
This research aimed to revitalize Mosau' Dance, a nearly extinct traditional dance from Bolaang Mongondow, through the creation of a new work entitled Sinungkudan Dance. Mosau' Dance is a celebratory dance of post-war warriors whose existence is currently fading in the Bolaang Mongondow region due to a lack of regeneration and the influence of modernization. This research employed a descriptive qualitative approach with a focus on choreographic analysis. The revitalization process was carried out through four stages: exploration, reconstruction, reinterpretation, and reactualization. The results indicate that revitalization through the creation of Sinungkudan Dance successfully provided a